Fluorite flotation purification method

By optimizing the composite collector system of oxidized paraffin soap and Zn-232 using response surface methodology, the performance deficiencies of single collectors and the optimization of process parameters in fluorite flotation were solved. This resulted in efficient, stable, and environmentally friendly fluorite separation, improved concentrate grade and adaptability, and is suitable for fluorite flotation purification.

CN121314802APending Publication Date: 2026-01-13CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511617626.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing fluorite flotation technologies face problems such as insufficient performance of single collectors, outdated methods for optimizing process parameters, and a lack of in-depth understanding of the mechanisms, making it difficult to efficiently separate complex low-grade fluorite ores, resulting in poor concentrate grade and stability.

Method used

A composite collector system consisting of oxidized paraffin soap and Zn-232 was used, and key parameters such as pH were optimized by response surface methodology to construct a dense hydrophobic membrane, thereby achieving efficient separation of gangue minerals such as fluorite and quartz.

Benefits of technology

It significantly improves the flotation separation efficiency and concentrate grade of fluorite, enhances the stability and adaptability of the concentrate, reduces reagent usage, meets the requirements of green mining, and is easy to apply industrially.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121314802A_ABST
    Figure CN121314802A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fluorite flotation, in particular to a fluorite flotation purification method. The method comprises the following steps that S1, fluorite raw ore is subjected to crushing and ore grinding treatment, and the ore grinding fineness is controlled to be-0.074 mm, and the content accounts for 80%-90%; s2, the ore powder obtained in the step S1 is prepared into ore pulp with a certain concentration, an inhibitor sodium silicate is added into the ore pulp, and stirring and pulp mixing are conducted; s3, the pH value of the ore pulp obtained in the step S2 is adjusted to 8-9 through a pH adjusting agent; and S4, a composite collecting agent composed of oxidized paraffin soap and Zn-232 is added into the ore pulp obtained in the step S3, flotation roughing operation is carried out, and an obtained foam product is fluorite concentrate. According to the composite collecting agent system and the optimization process provided by the invention, the technical indexes of fluorite flotation are improved in a leap-over manner. Under the optimal condition, the grade of the obtained fluorite concentrate stably reaches 80% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fluorite flotation technology, and more particularly to a method for fluorite flotation purification. Background Technology

[0002] Fluorite (calcium fluoride, CaF2), a crucial strategic non-metallic mineral resource indispensable to modern industry, is hailed as the "second rare earth," possessing irreplaceable application value in metallurgy, fluorochemicals, new energy, semiconductors, and precision manufacturing. Metallurgical-grade fluorite can be used as a flux to lower metal smelting temperatures; acid-grade fluorite is the core raw material for preparing hydrofluoric acid, leading to the development of high-value-added products such as fluorinated refrigerants, fluorinated polymers, fluorinated electronic chemicals, and lithium hexafluorophosphate (a key electrolyte for lithium-ion batteries). However, with the increasing depletion and consumption of high-quality, high-grade fluorite resources globally, mineral resources are exhibiting a severe trend of being "poor, fine-grained, and complex," meaning that the grade of natural fluorite is generally declining, the mineral grain size is fine, and it is closely associated with gangue minerals such as quartz, calcite, barite, and sulfides. This change in resource endowment makes the efficient and economical purification of low-grade complex fluorite ore to obtain high-purity acid-grade fluorite concentrate a key technological bottleneck for ensuring the safety and stability of the downstream industrial chain.

[0003] Flotation, as the most effective and widely used physicochemical method for separating fine-grained disseminated ores, is undoubtedly the core process for fluorite purification. Its basic principle is to utilize the differences in the physicochemical properties of mineral surfaces. By adding specific reagents (collectors, inhibitors, modifiers, etc.), the hydrophobicity of the target mineral (fluorite) is selectively enhanced, causing it to adhere to air bubbles and float to the surface of the pulp to form a froth product, thereby achieving separation from hydrophilic gangue minerals. However, the surface physicochemical properties of fluorite and common gangue minerals (such as quartz and calcite), especially in terms of zero charge point, surface ionic activity, and hydration energy, are often highly similar, resulting in minimal differences in their floatability. This poses a significant technical challenge to efficient flotation separation. To overcome this challenge, the selection and development of collectors has always been the focus of fluorite flotation research. Traditional fluorite flotation collectors mainly include anionic collectors, such as carboxylic acid collectors like sodium oleate and oxidized paraffin soap, as well as alkyl sulfonates and alkyl sulfates. Sodium oleate is widely used due to its strong collecting ability, but its selectivity is generally poor, and its separation effect on calcareous gangue minerals (such as calcite) is not ideal. Furthermore, it is susceptible to the effects of water hard ions (such as Ca2+). 2+ Mg 2+The significant impact of these factors leads to high consumption in actual slurries and drastic fluctuations in flotation indicators. While oxidized paraffin soap, as a cheaper alternative to sodium oleate, has lower costs, its complex active ingredients and unstable content of active components result in large fluctuations in collecting performance and selectivity, making it difficult to obtain stable, high-quality concentrates. A deeper problem lies in the inherent limitations of single-collector systems in terms of molecular structure design and mechanism of action. A single collector molecule typically has a strong affinity for only one type of active site on the mineral surface, making it difficult to achieve synergistic coverage and regulation of multiple sites on complex mineral surfaces. For example, although Zn-232 (whose main component is alkyl sulfonate) has some collecting ability for fluorite, its adsorption strength on the fluorite surface is limited, and its selective inhibition ability for quartz is insufficient, easily leading to excessive silicon content in the concentrate.

[0004] In summary, the existing fluorite flotation technology mainly faces the following core defects: (1) Insufficient performance of single collectors: It is difficult to balance the collection capacity, selectivity and stability, and cannot meet the high-efficiency separation requirements of complex low-grade fluorite ores; (2) Outdated process parameter optimization methods: Traditional single-factor optimization methods are difficult to handle the complex interaction between multiple parameters, resulting in the flotation process failing to reach the global optimal state; (3) Insufficient understanding of mechanisms: There is a lack of in-depth understanding of the action mechanism of reagents, especially composite collectors, on the mineral surface, which restricts the rational design of new reagents.

[0005] Therefore, the industry urgently needs to develop a novel composite collector system based on a synergistic mechanism, coupled with a systematic and scientific global optimization method, to construct a new, efficient, stable, and highly adaptable fluorite flotation process. This would enable the economical and environmentally friendly recovery of high-grade fluorite concentrate from low-grade complex ores. This not only has significant economic value but also plays a crucial role in safeguarding national strategic resource security. Summary of the Invention

[0006] The purpose of this invention is to address the aforementioned shortcomings of the prior art by proposing a fluorite flotation purification method that significantly improves flotation separation efficiency and concentrate quality.

[0007] The present invention provides a method for purifying fluorite by flotation, comprising the following steps: S1. The fluorite ore is crushed and ground to control the grinding fineness to be -0.074 mm with a content of 80%~90%; S2. Prepare the mineral powder obtained in step S1 into a slurry of a certain concentration, and add water glass as an inhibitor, and stir to adjust the slurry. S3. Use a pH adjuster to adjust the pH of the slurry obtained in step S2 to 7-10; S4. Add a composite collector consisting of oxidized paraffin soap and Zn-232 to the slurry obtained in step S3, and carry out flotation roughing operation to obtain frothy product, which is fluorite concentrate.

[0008] Furthermore, in step S1, the grinding fineness is -0.074 mm, accounting for 85% of the total content.

[0009] Furthermore, in step S2, the slurry concentration is 20%~30%.

[0010] Furthermore, the amount of the inhibitor water glass added is 800 g / t relative to the mass of the mineral powder.

[0011] Furthermore, in step S2, the inhibitor water glass is added in the form of a solution with a mass concentration of 5%.

[0012] Furthermore, in step S3, the pH adjuster is sodium carbonate or sulfuric acid.

[0013] Further, adjust the pH value to 8.5.

[0014] Further, in step S4, the mass ratio of oxidized paraffin soap to Zn-232 is (400~800):(600~1000).

[0015] Further, in step S4, the mass ratio of oxidized paraffin soap to Zn-232 is (600~650):(800~850).

[0016] Further, in step S4, the amount of the composite collector added is 1200~1800 g / t relative to the mass of the mineral powder.

[0017] This invention provides a highly adaptable and stable fluorite flotation purification pathway. By systematically optimizing the interaction of key parameters such as collector combination and pH value, it achieves efficient separation of fluorite from gangue minerals such as quartz and calcite in the roughing stage, obtaining high-grade fluorite concentrate. This invention utilizes the high selectivity of oxidized paraffin soap and the strong collecting ability of Zn-232, and through scientific component compounding and response surface methodology optimization, constructs a dense hydrophobic film on the fluorite surface, significantly improving flotation separation efficiency and concentrate quality.

[0018] The key technical point of this invention is: (1) Functional complementarity and synergistic adsorption effect of composite collector components: The core of this invention lies in constructing a composite collector system using oxidized paraffin soap and Zn-232. Oxidized paraffin soap, with its specific carboxylate functional groups, effectively adsorbs Ca2+ on the surface of fluorite. 2+The site exhibits high selectivity; while Zn-232 (alkyl sulfonate) possesses stronger collecting ability and diffusion rate. The two do not simply mix physically on the fluorite surface, but rather achieve synergistic co-adsorption through functional group complementarity and steric hindrance optimization, forming a denser and more stable hydrophobic layer. This overcomes the performance bottleneck of single collectors in terms of selectivity or collecting ability at the molecular level. This synergistic adsorption effect significantly enhances the hydrophobicity of the fluorite surface, thereby improving the adhesion efficiency of fluorite particles and bubbles, ultimately increasing the grade of fluorite in the concentrate.

[0019] (2) Multi-parameter global synergistic optimization based on response surface methodology: This invention abandons the traditional single-factor optimization method and innovatively adopts response surface methodology (RSM) to systematically optimize key process parameters such as the dosage of single and compound collectors and pH value. This method not only examines the independent influence of each factor, but more importantly, reveals the interaction between factors, thereby accurately determining the globally optimal process window, realizing the leap from "local optimization" to "system synergy", ensuring that the flotation process operates under optimal conditions, and maximizing the concentrate grade in the roughing stage.

[0020] (3) The mechanism of action revealed by the combination of multi-dimensional characterization and theoretical calculation: This invention comprehensively utilizes a variety of modern analytical techniques such as XPS, FTIR, contact angle, Zeta potential, and AFM to confirm the existence and manifestation of the synergistic adsorption effect from multiple dimensions, including elemental chemical state, functional group structure, wettability, surface charge, and microstructure. Furthermore, through density functional theory (DFT) calculations, the essential reason for the lower adsorption energy and more stable bonding of the composite collector on the fluorite surface is revealed from the electronic level, providing a solid theoretical basis for the synergistic effect and realizing a deep explanation from macroscopic phenomena to microscopic mechanisms, laying a scientific foundation for the feasibility and creativity of this technical solution.

[0021] Effects after implementation (1) Significantly improved flotation technical indicators: The composite collector system and optimized process provided by this invention have enabled a leapfrog improvement in the technical indicators of fluorite flotation. Under optimal conditions, the grade of the obtained fluorite concentrate is stably above 80%. This result is significantly better than that of a single collector system (the concentrate grade is usually below 60%), fully demonstrating the synergistic effect of oxidized paraffin soap and Zn-232 in improving the concentrate grade ("1+1>2" effect).

[0022] (2) Enhanced selectivity and stability of the flotation process: Thanks to the high selectivity of oxidized paraffin soap and the synergistic adsorption effect of the composite system, the process of this invention has extremely high separation efficiency for gangue minerals such as fluorite and quartz. The flotation process produces stable foam and the concentrate product has good purity consistency, effectively overcoming the shortcomings of single collectors (especially Zn-232) that cause serious entrainment of gangue minerals such as quartz and lead to fluctuations in concentrate grade. This makes the process more adaptable and more stable when dealing with complex and variable raw ore properties.

[0023] (3) Achieving both reagent cost and environmental benefits: Although this invention uses composite reagents, it achieves better flotation indicators with lower total reagent dosage through precise optimization using response surface methodology, thus avoiding excessive reagent use. At the same time, the main components of this system are all conventional flotation reagents, which are widely available and do not introduce expensive or environmentally unfriendly special reagents. This improves economic benefits while meeting the environmental protection requirements of green mines.

[0024] (4) The process flow is easy to industrialize: The response surface methodology used in this invention is an efficient and scientific process development tool that can significantly shorten the experimental cycle and quickly determine the globally optimal industrialization conditions. The determined flotation process flow is clear, the operating parameters are well-defined, and there is no need to rely on special or demanding equipment. The requirements for modifying existing flotation production lines are low, so it is very easy to achieve technology transfer and large-scale application in existing concentrators.

[0025] (5) Outstanding value in comprehensive utilization of mineral resources: This invention opens up a brand-new technical approach for the efficient recycling and utilization of complex fluorite resources with low grade and fine-grained dissemination. Through technological innovation, the resource utilization rate has been greatly improved and the service life of mines has been extended. It has important strategic significance for ensuring the supply security of my country's strategic fluorine resources, and has excellent environmental, social and economic benefits. Attached Figure Description

[0026] Figure 1 The response surface plots of pH value, Zn-232 dosage and oxidized paraffin soap dosage to fluorite concentrate grade; Figure 2 Ca 2p spectra of fluorite with different collectors: (a) pure fluorite; (b) with Zn-232 added; (c) with oxidized paraffin soap added; (d) with composite collector added; Figure 3 Infrared spectra of different minerals before and after adsorption of reagents: (a) fluorite; (b) quartz; Figure 4 The changes in contact angles of fluorite and quartz after the addition of Zn-232, oxidized paraffin soap and composite collector; Figure 5Analysis of the surface potential dynamics of fluorite minerals before and after adsorption by three reagents: Zn-232, oxidized paraffin soap, and a composite collector; Figure 6 Atomic force microscopy images of fluorite surfaces before and after the addition of different collectors; Figure 7 Models adsorbed on the (111) crystal facet of fluorite: (a) sodium oleate; (b) sodium petroleum sulfonate; (c) composite collector; Figure 8 A schematic diagram of the adsorption of the composite collector on the surface of fluorite (111). Detailed Implementation

[0027] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments.

[0028] Example 1 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0029] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0030] (3) Use a pH adjuster to adjust the pH of the slurry to 8.5.

[0031] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 800 g / t and the amount of oxidized paraffin soap is 600 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade is 80.23% after testing.

[0032] Example 2 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0033] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0034] (3) Use a pH adjuster to adjust the pH of the slurry to 10.

[0035] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 800 g / t and the amount of oxidized paraffin soap is 400 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 73.32%.

[0036] Example 3 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0037] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0038] (3) Use a pH adjuster to adjust the pH of the slurry to 7.

[0039] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 800 g / t and the amount of oxidized paraffin soap is 400 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 71.56%.

[0040] Example 4 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0041] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0042] (3) Use a pH adjuster to adjust the pH of the slurry to 8.5.

[0043] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 600 g / t and the amount of oxidized paraffin soap is 400 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 69.47%.

[0044] Example 5 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0045] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0046] (3) Use a pH adjuster to adjust the pH of the slurry to 7.

[0047] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 1000 g / t and the amount of oxidized paraffin soap is 600 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 72.32%.

[0048] Example 6 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0049] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0050] (3) Use a pH adjuster to adjust the pH of the slurry to 7.

[0051] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 800 g / t and the amount of oxidized paraffin soap is 800 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 78.68%.

[0052] Example 7 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0053] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0054] (3) Use a pH adjuster to adjust the pH of the slurry to 10.

[0055] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 600 g / t and the amount of oxidized paraffin soap is 600 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade is 70.77% after testing.

[0056] Example 8 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0057] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0058] (3) Use a pH adjuster to adjust the pH of the slurry to 10.

[0059] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 1000 g / t and the amount of oxidized paraffin soap is 600 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 76.86%.

[0060] Example 9 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0061] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0062] (3) Use a pH adjuster to adjust the pH of the slurry to 8.5.

[0063] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 800 g / t and the amount of oxidized paraffin soap is 600 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade is 80.65% after testing.

[0064] Example 10 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0065] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0066] (3) Use a pH adjuster to adjust the pH of the slurry to 8.5.

[0067] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 1000 g / t and the amount of oxidized paraffin soap is 800 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 77.69%.

[0068] Example 11 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0069] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0070] (3) Use a pH adjuster to adjust the pH of the slurry to 8.5.

[0071] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 600 g / t and the amount of oxidized paraffin soap is 800 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 74.14%.

[0072] Example 12 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0073] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0074] (3) Use a pH adjuster to adjust the pH of the slurry to 10.

[0075] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 800 g / t and the amount of oxidized paraffin soap is 800 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 76.63%.

[0076] Example 13 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0077] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0078] (3) Use a pH adjuster to adjust the pH of the slurry to 7.

[0079] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 600 g / t and the amount of oxidized paraffin soap is 600 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade was tested and found to be 71.23%.

[0080] Example 14 (1) Take fluorite ore, crush and grind it to -0.074 mm content of 85%, and prepare flotation slurry with a slurry concentration of 25%.

[0081] (2) Add water glass inhibitor to the slurry at a dosage of 800 g / t and stir for 2 minutes.

[0082] (3) Use a pH adjuster to adjust the pH of the slurry to 8.5.

[0083] (4) Add a composite collector to the slurry, wherein the amount of Zn-232 is 1000 g / t and the amount of oxidized paraffin soap is 400 g / t. Stir for 3 minutes to obtain flotation froth, which is the final fluorite concentrate product. The concentrate grade is 76.75% after testing.

[0084] Comparative Example 1 Using only Zn-232, the dosage was adjusted to 600 g / t, 800 g / t, and 1000 g / t, with other parameters the same as in Example 1. Testing showed that the optimal concentrate grade of 68% was obtained when the dosage of Zn-232 was 800 g / t.

[0085] Comparative Example 2 Using a single paraffin oxidized soap at a dosage of 600 g / t, the dosage was adjusted to 600 g / t, 800 g / t, and 1000 g / t, with other parameters remaining the same as in Example 1. Testing showed that when the single paraffin oxidized soap dosage was 600 g / t, the optimal concentrate grade was 52%.

[0086] Table 1 Process parameters and concentrate grade of the examples

[0087] Figure 1 The response surface plots of pH, Zn-232 dosage, and oxidized paraffin soap dosage on the grade of fluorite concentrate are shown. Through quadratic regression model analysis, the effects of collector dosage and pH on concentrate grade have a high goodness of fit. This model can accurately describe the variation law of experimental data. Based on the model optimization results, the optimal flotation conditions were determined to be 840 g / t of Zn-232 dosage, 643 g / t of oxidized paraffin soap dosage, and pH value of 8.5. Under these conditions, the grade of fluorite concentrate can reach 80%, which is well verified by the data from Example 1.

[0088] like Figure 2 As shown, the Ca 2p spectrum on the surface of fluorite exhibits typical spin-orbit splitting characteristics, where Ca 2p 3 / 2 and Ca 2p 1 / 2 The main peaks are located at 347.91 eV and 351.78 eV, respectively, which is highly consistent with the XPS characteristic peak positions of natural fluorite reported in the literature. After the action of Zn-232 collector, Ca 2p 3 / 2 and Ca 2p 1 / 2 The binding energies shifted to lower energies, reaching 347.78 eV and 351.38 eV respectively. This decrease in binding energy indicates a chemisorption reaction between Zn-232 and Ca atoms on the fluorite surface, but this interaction is relatively weak. In contrast, after treatment with oxidized paraffin soap, the Ca 2p... 3 / 2 and Ca 2p 1 / 2 The peaks shifted to 347.78 eV and 351.42 eV, respectively, while Ca 2p 1 / 2 The relative intensity of the peaks decreased significantly, indicating that the oxidized paraffin soap formed more stable chemical bonds on the fluorite surface. After treatment with the mixed collector, Ca 2p 3 / 2 and Ca 2p 1 / 2 The peaks shifted to 347.68 eV and 351.28 eV, with binding energy shifts greater than those observed after treatment with a single collector. This phenomenon indicates that the adsorption strength of the mixed collector on the fluorite surface is superior to that of the single collector system, possibly due to a synergistic adsorption effect between the two collectors on the fluorite surface. XPS analysis confirmed the chemical interaction between the collector and the fluorite surface and provided crucial experimental evidence for understanding the synergistic mechanism of the mixed collector.

[0089] Figure 3(a) shows the infrared spectral characteristics of fluorite before and after the treatment with the collector. No obvious organic group characteristic peaks were observed in the infrared spectrum of untreated fluorite; its spectral characteristics were mainly dominated by the lattice vibrations of CaF2. After Zn-232 treatment, a peak at 2922.75 cm⁻¹ appeared in the spectrum. -1 and 2852.72 cm -1 The characteristic absorption peaks at [value] correspond to the asymmetric and symmetric stretching vibrations of the C–H bond, respectively, indicating that the organic functional groups in Zn-232 underwent chemisorption on the fluorite surface. After treatment with paraffin soap oxide, the peak at 1639 cm⁻¹... -1 At (C=O stretching vibration) and 2918 cm -1 and 2850 cm -1 The absorption intensity at the (C–H stretching vibration) site was significantly enhanced, confirming that the –CH3 and –CH2– groups in the collector interacted with the Ca on the fluorite surface. 2+ Chemical bonding occurred. Notably, the intensity changes of the aforementioned characteristic peaks were more significant after the action of the mixed collector, indicating a stronger interaction between the mixed collector and the fluorite surface. Figure 3 (b) The infrared spectral characteristics of quartz after treatment with different collectors are shown. The results indicate that no new characteristic absorption peaks appeared in the infrared spectrum of quartz after treatment with sodium oleate, paraffin oxidized soap, and their mixed collectors. This suggests that these collectors only undergo physical adsorption on the quartz surface, and the adsorption strength is weak. Comprehensive analysis shows that the mixed collectors exhibit adsorption on both fluorite and quartz surfaces, but their adsorption capacity for fluorite is significantly stronger than that for quartz, demonstrating good selectivity. Zn-232 showed no significant difference in selectivity for fluorite and quartz, while paraffin oxidized soap exhibited high selectivity, with strong adsorption for fluorite and almost no adsorption for quartz. Furthermore, the experimental results show that both collectors can simultaneously adsorb on the fluorite surface; the specific mechanism of this phenomenon will be further elucidated in subsequent discussions.

[0090] Figure 4The results show that the contact angle of fluorite significantly increased after the application of a single collector, confirming that the collector molecules were effectively adsorbed on the fluorite surface, reducing its surface energy and thus enhancing hydrophobicity. In contrast, the contact angle of quartz showed a smaller change, indicating that the adsorption of the collector on the quartz surface was weaker. This difference mainly stems from the significant differences in the surface chemistry of fluorite and quartz; the fluorite surface has more active sites, enabling stronger interactions with collector molecules. Specifically, the addition of Zn-232 increased the contact angles of both fluorite and quartz, while the addition of paraffin oxide soap increased the contact angle of fluorite but decreased the contact angle of quartz. This phenomenon indicates that both collectors can adsorb on the fluorite surface, thereby enhancing its floatability. However, the adsorption of Zn-232 on the quartz surface may trap some quartz, leading to a decrease in the grade of fluorite concentrate. Paraffin oxide soap may have an inhibitory effect on the quartz surface or only cause a small amount of adsorption. Notably, after the mixed collector was applied, the contact angles of fluorite and quartz reached 131.4° and 15.1°, respectively. The contact angle of fluorite was significantly larger than that under the single collector, indicating that the mixed collector had a stronger adsorption capacity on the fluorite surface and could more effectively improve its buoyancy. In summary, the mixed collector exhibited a significant selective modulation effect on the surface wettability of fluorite and quartz, and its performance advantage stemmed from the synergistic effect of the strong collecting ability of Zn-232 and the high selectivity of oxidized paraffin soap. The contact angle test results further confirmed that the two collectors could co-adsorb on the fluorite surface, thereby significantly enhancing its hydrophobicity. This phenomenon may be related to the adsorption configuration of the two collectors on the fluorite surface and their interaction; the specific mechanism will be further investigated later.

[0091] Figure 5 The results showed that the fluorite surface exhibited a stable negative charge under different pH conditions, and the absolute value of its negative potential gradually decreased with increasing pH. This phenomenon can be attributed to the increase in hydroxide ion concentration (OH-) due to the rising pH. -The increased adsorption of these collectors on the fluorite surface neutralized some of the surface negative charge. After adding the collectors, the mixed collectors, Zn-232, and oxidized paraffin soap all significantly altered the zeta potential of fluorite, confirming the adsorption effect of these agents on the fluorite surface. Specifically, the Zn-232 collector rapidly increased the fluorite surface potential to approximately -40 mV under acidic conditions, reaching a maximum at pH=9, and then decreasing. The oxidized paraffin soap collector showed a similar trend, but its effect on increasing the fluorite potential was more significant at pH=9, indicating that these two agents have the strongest adsorption capacity under weakly alkaline conditions. Notably, at pH=7, the zeta potential of fluorite after the action of the mixed collector was -55 mV, a significant negative shift compared to the single agent, further confirming the stronger adsorption capacity of the mixed collector on the fluorite surface. Comprehensive analysis revealed that the mixed collector increased the negative charge density on the fluorite surface, a phenomenon attributed to the increased presence of collector molecules on the Ca2+ surface. 2+ Adsorption occurred at the active sites. Experimental results showed that there was a synergistic effect between the two agents in the mixed collector system, rather than mutual inhibition. This synergistic effect may have originated from the co-adsorption of the two collector molecules on the fluorite surface and their interaction, which improved the overall adsorption effect.

[0092] like Figure 6 As shown, the surface morphology of untreated fluorite is relatively smooth with low surface roughness, providing a benchmark for subsequent morphological changes caused by reagent adsorption. Comparative analysis of AFM images after reagent treatment reveals a distinct raised structure on the fluorite surface, caused by chemisorption of the reagent on the mineral surface. Comparison of surface morphology and height data after Zn-232 and oxidized paraffin soap treatment shows that Zn-232 treatment results in greater surface roughness, indicating higher adsorption capacity. This result is consistent with observations of higher concentrate yields obtained by the Zn-232 system in flotation experiments. Notably, the fluorite surface treated with the composite collector exhibits not only higher adsorption density but also significantly greater adsorption height than the single-reagent system. The higher adsorption density confirms that the two reagents can co-adsorb on the fluorite surface, resulting in a synergistic effect. Studies have shown that collector combinations composed of long carbon chains or benzene ring structures generally exhibit better selectivity; therefore, the higher adsorption height observed in the composite collector system further confirms its excellent selectivity. AFM analysis results showed that the adsorption capacity and adsorption height of the composite collector system on the fluorite surface were significantly higher than those of the single-agent system, directly demonstrating that the composite collector has stronger collecting performance. This finding provides important experimental evidence for understanding the synergistic mechanism of the composite collector.

[0093] The anisotropy of charge distribution on the fluorite surface mainly stems from the differences in atomic composition across its different crystal planes, with the (111) plane exhibiting stronger electronegativity due to the exposure of F atoms. Based on this, a molecular dynamics model of the fluorite (111) surface was constructed, and the adsorption behavior of pharmaceuticals on this surface was simulated. Figure 7 The model shown illustrates the adsorption configuration of the agent on the fluorite (111) surface from two perspectives. Considering that both Zn-232 and oxidized paraffin soap are multi-component systems, the main active ingredients—oleic acid and alkyl sulfonate—were selected as model molecules to represent the actual interaction between the agent and fluorite. A quantitative comparative study was conducted on the energy changes between the single-agent system and the composite collector system by calculating the adsorption energy. The results show that the adsorption energy of the composite collector system is significantly lower than that of the single-agent system. This result confirms the performance advantage of the composite collector system from an energy perspective. The reduction in adsorption energy can be attributed to the synergistic adsorption effect of the components in the composite collector on the fluorite surface. This effect may originate from the spatial complementarity or electronic interaction between different agent molecules. As shown in Table 2, in the single-reagent system, the adsorption energy of oleic acid on the fluorite surface is -1.09 eV, and that of alkyl sulfonate on the fluorite surface is -1.17 eV. However, when these two reagents are mixed, the adsorption energy of the system decreases to -2.72 eV, which is larger in absolute terms than that of the single-reagent system. This result indicates that a synergistic effect occurs between Zn-232 and oxidized paraffin soap, leading to a change in the adsorption energy of the composite collector system. The decrease in adsorption energy means a stronger interaction between the composite collector and the fluorite surface. This may be because the two reagent molecules form a more stable adsorption configuration on the fluorite surface, or it may be due to the increased overall adsorption strength achieved through intermolecular interactions. The composite collector system exhibits superior flotation performance, a result consistent with experimentally observed flotation behavior.

[0094] Table 2 Adsorption energies of different reagents on fluorite surface

[0095] This patent elucidates a synergistic adsorption mechanism between Zn-232 and oxidized paraffin soap on the fluorite surface during flotation. Specifically, Zn-232 preferentially adsorbs Ca on the fluorite surface. 2+Active sites are formed, creating a calcium oleate monolayer that inhibits further adsorption of Zn-232. Subsequently, due to the higher adsorption energy of oxidized paraffin soap, it can continue to adsorb Zn-232 on the already adsorbed fluorite surface, filling the gaps between Zn-232 molecules. This synergistic adsorption effect significantly enhances the hydrophobicity of the fluorite surface, thereby improving the adhesion efficiency of fluorite particles to bubbles and ultimately increasing the grade of fluorite in the concentrate. To elucidate this mechanism, a schematic diagram of the adsorption of mixed collectors on the mineral surface was constructed. Figure 8 As shown in the model, in the mixed collector system, Zn-232 forms a monolayer on the fluorite surface through chemisorption, while oxidized paraffin soap further modifies the surface properties through intercalation adsorption. This synergistic effect significantly enhances the hydrophobicity of the fluorite surface, promoting the flotation of fluorite particles. Simultaneously, due to the inhibitory effect of water glass, only a small amount of collector adsorption occurs on the quartz surface, thus achieving efficient separation of fluorite and quartz. This mechanism not only explains the synergistic effect of the mixed collector but also provides a theoretical basis for optimizing the fluorite flotation process.

[0096] For any points not covered above, existing technologies shall apply.

[0097] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for purifying fluorite by flotation, characterized in that, Includes the following steps: S1. The fluorite ore is crushed and ground to control the grinding fineness to be -0.074 mm with a content of 80%~90%; S2. Prepare the mineral powder obtained in step S1 into a slurry of a certain concentration, and add water glass as an inhibitor, and stir to adjust the slurry. S3. Use a pH adjuster to adjust the pH of the slurry obtained in step S2 to 7-10; S4. Add a composite collector consisting of oxidized paraffin soap and Zn-232 to the slurry obtained in step S3, and carry out flotation roughing operation to obtain frothy product, which is fluorite concentrate.

2. The fluorite flotation purification method as described in claim 1, characterized in that, In step S1, the grinding fineness is -0.074 mm, and the content is 85%.

3. The fluorite flotation purification method as described in claim 1, characterized in that, In step S2, the slurry concentration is 20%~30%.

4. The fluorite flotation purification method as described in claim 1, characterized in that, The amount of water glass added as an inhibitor is 800 g / t relative to the mineral powder mass.

5. The fluorite flotation purification method as described in claim 1, characterized in that, In step S2, the inhibitor water glass is added in the form of a solution with a mass concentration of 5%.

6. The fluorite flotation purification method as described in claim 1, characterized in that, In step S3, the pH adjuster is sodium carbonate or sulfuric acid.

7. The fluorite flotation purification method as described in claim 1, characterized in that, Adjust the pH to 8.

5.

8. The fluorite flotation purification method as described in claim 1, characterized in that, In step S4, the mass ratio of oxidized paraffin soap to Zn-232 is (400~800):(600~1000).

9. The fluorite flotation purification method as described in claim 1, characterized in that, In step S4, the mass ratio of oxidized paraffin soap to Zn-232 is (600~650):(800~850).

10. The fluorite flotation purification method as described in claim 1, characterized in that, In step S4, the amount of the composite collector added is 1200~1800 g / t relative to the mass of the mineral powder.